The isolation of Behavioral Analysis in Brazil: a bibliometric analysis (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
This paper describes bibliometric research on the communication of Behavioral Analysis and other areas of psychology in the Brazilian literature. The references of the three major national journals on Behavioral Analysis and one relevant general national journal of psychology, were analyzed and used as a comparative analysis. In journals of behavioral analysis it was found a similar percentage of references to texts on Behavioral Analysis and to texts on other areas of knowledge (45,4% and 45,9%, respectively). In the general journal, 89.7% of the references were made to texts from other areas of knowledge and only 2.9% of references were made to texts on Behavioral Analysis, the majority of them in articles on this same area. The results suggest that the general literature on psychology practically ignore the contributions of Behavioral Analysis, constituting a specific form of isolation of the Behavior Analysis, in the national literature. Suggestions are presented as to how to reduce this isolation
Keywords: behavioral analysis; scientific communication; bibliometric; psychology; reflection & criticism